A new Acanthotetilla sponge from the Southwest Atlantic (Tetillidae, Spirophorina, Tetractinellida, Demospongiae), with an updated discussion on the diversity, distribution and morphologic characters of Acanthotetilla spp. - Fernandez, Julio C.c.; Hajdu, Eduardo (Zootaxa, 2024)
Acanthotetilla is a genus of tetillid sponges diagnosed by the presence of medium-sized, heavily spined oxeas, which are known as “megacanthoxeas” (or simply acanthoxeas). Currently, seven species are known worldwide: three from the Western Atlantic (A. gorgonosclera, A. rocasensis and A. walteri), three from the Western Indian (A. hemisphaerica, A. enigmatica and A. seychellensis) and one from the Western Pacific (A. celebensis). A megacanthoxea-bearing specimen was obtained from the Fernando de Noronha Archipelago, Southwest Atlantic, in 2016. It is described here as a new Acanthotetilla, namely, A. noronhensis sp. nov. This new species has two categories of megacanthoxeas, like A. celebensis from Celebes/Sulawesi Sea, Indonesia. However, the former differs from the latter, as well as from other congeners, by the combination of endolithic habit and spiculation. Acanthotetilla noronhensis sp. nov. is known on the basis of a single specimen from a large collection of sponges from Fernando de Noronha. Besides, the species was not found in other sponge collections from different areas of Brazil, including oceanic areas. Thus, the new species has probably a low abundance and restricted distribution, alike all other known Acanthotetilla species, aside A. celebensis, which (regardless its low abundance) occurs in a large sector of the western Pacific. Despite A. noronhensis sp. nov. and A. celebensis being separated by a wide geographic distance, the unique occurrence of two categories of megacanthoxeas might suggest closer phylogenetic relationship and biogeographic history as well. A wider discussion on the diversity, distribution and morphologic characters of Acanthotetilla spp. is supplied in this study. A comparative taxonomic table and a taxonomic identification key to Acanthotetilla spp. is supplied as well.